Thyroid dysfunction in patients of metabolic syndrome: A study from a tertiary care center in India - Gupta, Ritu; Vijayan, Akhil K; Choudhary, Sushma (Asian Journal of Medical Sciences, 2021)
Background: Metabolic syndrome is characterized by hypertension, dyslipidemia, central obesity, glucose intolerance, insulin resistance. Thyroid hormone acts as general pacemaker, accelerating metabolic process and may be associated with metabolic syndrome. There is no information available in literature regarding the prevalence and association of thyroid dysfunction in metabolic syndrome in this central region of the country. Aims and Objective: To estimate the prevalence of thyroid dysfunction in patients of metabolic syndrome. Materials and Methods: It is a duration based prospective cross sectional study including 200 patients of metabolic syndrome. A detailed history, clinical examination and relevant investigations including serum Free T4 (FT4), Free T3 (FT3), Thyroid Stimulating Hormone (TSH) were done. Range, frequencies, percentage, mean, standard deviation and P value were calculated. P value of < 0.05 was taken as significant. Results: Prevalence of thyroid dysfunction in metabolic syndrome patients was 28.5%. Prevalence of subclinical and overt hypothyroidism was 18.5% and 8.5% respectively. In patients with both metabolic syndrome and thyroid dysfunction, most common components associated are diabetes mellitus and hypertriglyceridemia. Conclusion: Thyroid dysfunction is significantly common in metabolic syndrome patients. It should be aggressively detected and treated in these patients for better outcome.